Travels through the interior provinces of Columbia : in two volumes : vol II, wiith engravings / by Colonel J. P. Hamilton, late chief commissioner from his britannic majesty to the Republic of Columbia (1827)
"Doctor Borrero now congratulated us on our safe arrival at his native place. His father, who, as I before stated, was a Spaniard, had settled with his family in La Plata, after serving for some years as an officer in the Spanish army. Here he accumulated a large fortune ; leaving at his death 80.000 dollars to be divided amongst his children, besides considerable landed property. The Doctor, who was truly generous, had contrived to get through a great deal of his share, but he still possessed large estates. Our quarters in La Plata were very snug, and we were quite charmed with the beauty and variety of the flowers which were cultivated in the gardens ; orange-trees were in great abundance, some in flower and others bearing fruit ; the former extremely fragrant"